D-cysteine desulfhydrase DCD1 participates in tomato resistance against Botrytis cinerea by modulating ROS homeostasis - Yuqi Zhao; Kangdi Hu; Gaifang Yao; Siyue Wang; Xiangjun Peng; Conghe Zhang; Dexin Zeng; Kai Zong; Yaning Lyu; Hua Zhang (Vegetable Research)
Tomato is one of the most popular horticultural crops, and many commercial tomato cultivars are particularly susceptible to Botrytis cinerea. Hydrogen sulfide (H2S) is an important gaseous molecule in various plant stress responses. In this study, it was found that endogenous H2S increases in tomato leaves in response to B. cinerea infection, along with a 3.8-fold increase in gene expression of DCD1 which encodes a H2S-generating enzyme D-cysteine desulfhydrase 1 in tomato at 3 DPI. Then we investigated the role of DCD1 in resistance of tomato leaves and fruits to B. cinerea. The mutation of DCD1 by CRIPSR/Cas9 greatly reduced the resistance of tomato leaves and breaker and red fruits to B. cinerea accompanied with increased reactive oxygen species (ROS) especially hydrogen peroxide (H2O2) and malondialdehyde (MDA) content increased by 1.2 and 1.4 times respectively at 5 DPI of leaves. Further investigation showed that DCD1 mutation caused decreased activity of antioxidative enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT) in both leaves and fruits, in particular, CAT activity in dcd1 mutant was 25.0 % and 41.7 % of that in WT at leaves and red fruits at 5 DPI. DCD1 mutation also caused decreased expression of defense-related genes PAL (encoding phenylalanine ammonia-lyase) and PUB24, and their expression in the dcd1 red fruit is approximately 1.3 and 1.8 times higher than in wild-type red fruit at 5 DPI, respectively. Thus, the work emphasizes the positive role of DCD1 and H2S in plant responses to necrotrophic fungal pathogens. In addition, the work provides strong evidence that fruit at ripened stage is more susceptible to B. cinerea infection compared with green fruit, suggesting that senescence of plant tissues is more favorable to B. cinerea infection.